ANALISIS ISI KASUS PEMALSUAN DOKUMEN FAM PADA PODCAST “FIFA DENDA FAM & 7 PEMAIN” DI KANAL YOUTUBE @ASTROARENA - Ahmad Alfath, Rizki; Nurhaqiqi, Hanna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The issue of heritage player eligibility has become a major topic in Southeast Asian football following FIFA's sanctions against the Football Association of Malaysia (FAM) over alleged document falsification involving seven naturalized players. The controversy generated extensive public discussion, including media narratives that shaped audience perceptions of the case. This study aims to analyze the narrative construction used by the hosts of The Astro Arena “FIFA Denda FAM & 7 Pemain” podcast in discussing the controversy. The research employs a qualitative content analysis approach based on Krippendorff's framework, emphasizing inference from text to its context. The research object is the podcast episode discussing FIFA's sanctions against FAM, while the units of analysis consist of sampling units (the selected podcast episode), recording units (host statements), and context units (the surrounding discussion that provides meaning to each statement). The findings reveal four narrative categories: contextualization, criticism, passive defensive, and speculative narratives. Among these, criticism is the most dominant narrative. However, the criticism is not solely directed at FIFA but also at FAM, particularly regarding its lack of transparency and public communication in the heritage player naturalization process. The study further finds that criticism functions as a communication strategy to encourage organizational transparency rather than merely assigning blame. Meanwhile, passive defensive and speculative narratives are employed to prevent premature public judgment while acknowledging various perspectives surrounding the controversy. Overall, the podcast constructs a narrative that positions transparency as the primary means for restoring FAM's public legitimacy amid the crisis.